Interface-state density estimation of n-type nanocrystalline FeSi2/p-type Si heterojunctions fabricated by pulsed laser deposition - Adison Nopparuchikun; Nathaporn Promros; Phongsaphak Sittimart; Peeradon Onsee; Asanlaya Duangrawa; Sakmongkon Teakchaicum; Tomohiro Nogami; Tsuyoshi Yoshitake (My University, 2017)
By utilizing pulsed laser deposition (PLD), heterojunctions comprised of n-type nanocrystalline (NC) FeSi2 thin films and p-type Si substrates were fabricated at room temperature in this study. Both dark and illuminated current density–voltage (J–V) curves for the heterojunctions were measured and analyzed at room temperature. The heterojunctions demonstrated a large reverse leakage current as well as a weak near-infrared light response. Based on the analysis of the dark forward J–V curves, at the V value ⩽ 0.2 V, we show that a carrier recombination process was governed at the heterojunction interface. When the V value was > 0.2 V, the probable mechanism of carrier transportation was a space-charge limited-current process. Both the measurement and analysis for capacitance–voltage–frequency (C–V–f ) and conductance–voltage–frequency (G–V–f ) curves were performed in the applied frequency (f ) range of 50 kHz–2 MHz at room temperature. From the C–V–f and G–V–f curves, the density of interface states (Nss) for the heterojunctions was computed by using the Hill–Coleman method. The Nss values were 9.19 × 1012 eV−1 cm−2 at 2 MHz and 3.15 × 1014 eV–1 cm–2 at 50 kHz, which proved the existence of interface states at the heterojunction interface. These interface states are the probable cause of the degraded electrical performance in the heterojunctions.
Keywords: Nanocrystalline material; Pulsed Laser Deposition; Atmospheric temperature range; Semiconductor materials and interfaces